2014
DOI: 10.4236/ajps.2014.520321
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination and Effects of Three Watering Regimes on the Growth of <i>Dialium guineense</i> (Wild) Seedlings

Abstract: The effectiveness of three pre-germination treatments in breaking dormancy of the seeds of Dialum guineense and effects of three watering regimes on the growth performance of the seedlings were investigated. The pre-germination treatments were: soaking in hot water for 10 seconds and cooling down in cold water (T 1 ), soaking in cold water for 24 hours (T 2 ), soaking in running water for 48 hours (T 3 ) and control (T 4 ), while watering regimes include: watering once daily in the morning (W 1 ), watering onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
2
3
0
1
Order By: Relevance
“…2). This is similar to the findings of Oladeji et al 5 who reported that plant height of Dialium guineense was not significantly affected by watering regime. Seedlings subjected to watering once a week had the highest plant height of 11.75 cm followed closely by those watered everyday (11.25 cm).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2). This is similar to the findings of Oladeji et al 5 who reported that plant height of Dialium guineense was not significantly affected by watering regime. Seedlings subjected to watering once a week had the highest plant height of 11.75 cm followed closely by those watered everyday (11.25 cm).…”
Section: Resultssupporting
confidence: 92%
“…Vegetable species are plants of great nutritional and medicinal importance especially to man, even though some of these species are gradually being eroded. Physiological and ecological information needed on these plant species include flowering and fruiting patterns, seed germination and growth requirement in order to facilitate domestication and improvement of their potentials 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduced girth found in water deficit O. gratissimum could be because of dehydration of the plant which must have caused reduced photosynthetic activities of the plants [32] . The findings of this study corroborate that of Olajide et al [33] who reported a significant difference in Dialium guineense seedling girth due to the application of different watering regimes. However, a contrasting result was submitted by Gbadamosi [3] who reported that girth of seedlings was not significantly (p < 0.05) different under watering regimes and water quantity.…”
Section: Effects Of Water Stress On Growth Characters Of O Gratissimumsupporting
confidence: 92%
“…Taub. (Caesalpinoideae) Alves et al (2013) Investigaciones sobre D. guineense han reportado longitudes del tallo de 10.4 cm a 90 después del trasplante (Olajide et al, 2014) y de 9 cm a 177 días (Orhue, 1997) para la misma especie africana.…”
Section: Discusión Germinación Y Crecimiento De Tallo Raíz Y Hojasunclassified